Impact of Computer-based Instruction on Academic Achievements of Secondary Schools' students of Mathematics in District Peshawar Pakistan. - Khan, Humayun; Khan, Wazim (Dialogue (Pakistan))
The primary purpose of this study was to explore and approve an appropriate instructional method for teaching mathematics, utilising Computer-based instructional method in the secondary school mathematics classroom in the government schools of district Peshawar Pakistan. Purposive sampling technique was exercised. Participants of this study involved the 9th-grade 350 students. The 'Post-test only Control Group Experimental Design' was used. Computer-based instructional lessons were administered to the experimental group while the control group got the conventional method of teaching. Independent sample t-test, was used for data analysis. CBI was concluded significantly better in comparison. Therefore, it is recommended at secondary school level in mathematics on the basis of the results of this study in the government schools of district Peshawar. However, the existing teachers must be trained through refresher courses in integrating computer technology into teaching and facilities must be provided to satisfy the students' needs and course objectives.